Structure, Function, and Evolution of The Thiomonas spp. Genome - Arsene-Ploetze, F.; Koecheler, S.; Marchal, M.; Coppee, J.; Chandler, M.; Bonnefoy, V.; Brochier-Armanet, C.; Barakat, M.; Barbe, V.; Battaglia-Brunet, F.; Bruneel, O.; Bryan, Christopher (Public Library of Science, 2010)
Bacteria of the Thiomonas genus are ubiquitous in extreme environments, such as arsenic-rich acid mine drainage (AMD). The genome of one of these strains, Thiomonas sp. 3As, was sequenced, annotated, and examined, revealing specific adaptations allowing this bacterium to survive and grow in its highly toxic environment. In order to explore genomic diversity as well as genetic evolution in Thiomonas spp., a comparative genomic hybridization (CGH) approach was used on eight different strains of the Thiomonas genus, including five strains of the same species. Our results suggest that the Thiomonas genome has evolved through the gain or loss of genomic islands and that this evolution is influenced by the specific environmental conditions in which the strains live.